Coordinated activation of AMP‐activated protein kinase, extracellular signal‐regulated kinase, and autophagy regulates phorbol myristate acetate‐induced differentiation of SH‐SY5Y neuroblastoma cells. (14th November 2014) - Zogovic, Nevena; Tovilovic‐Kovacevic, Gordana; Misirkic‐Marjanovic, Maja; Vucicevic, Ljubica; Janjetovic, Kristina; Harhaji‐Trajkovic, Ljubica; Trajkovic, Vladimir
Abstract We explored the interplay between the intracellular energy sensor AMP‐activated protein kinase (AMPK), extracellular signal‐regulated kinase (ERK), and autophagy in phorbol myristate acetate (PMA)‐induced neuronal differentiation of SH‐SY5Y human neuroblastoma cells. PMA‐triggered expression of neuronal markers (dopamine transporter, microtubule‐associated protein 2, β‐tubulin) was associated with an autophagic response, measured by the conversion of microtubule‐associated protein light chain 3 (LC3)‐I to autophagosome‐bound LC3‐II, increase in autophagic flux, and expression of autophagy‐related (Atg) proteins Atg7 and beclin‐1. This coincided with the transient activation of AMPK and sustained activation of ERK. Pharmacological inhibition or RNA interference‐mediated silencing of AMPK suppressed PMA‐induced expression of neuronal markers, as well as ERK activation and autophagy. A selective pharmacological blockade of ERK prevented PMA‐induced neuronal differentiation and autophagy induction without affecting AMPK phosphorylation. Conversely, the inhibition of autophagy downstream of AMPK/ERK, either by pharmacological agents or LC3 knockdown, promoted the expression of neuronal markers, thus indicating a role of autophagy in the suppression of PMA‐induced differentiation of SH‐SY5Y cells. Therefore, PMA‐induced neuronal differentiation of SH‐SY5Y cells depends on a complex interplay between AMPK, ERK, and autophagy, in which the stimulatory effects of AMPK/ERK signaling are counteracted by the coinciding autophagic response. <boxed-text content-type="graphic" id="jnc12980-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> Phorbol myristate acetate (PMA) induces the expression of dopamine transporter, microtubule‐associated protein 2, and β‐tubulin, and subsequent neuronal differentiation of SH‐SY5Y neuroblastoma cells through AMP‐activated protein kinase (AMPK)‐dependent activation of extracellular signal‐regulated kinase (ERK). The activation of AMPK/ERK axis also induces the expression of beclin‐1 and Atg7, and increases LC3 conversion, thereby triggering the autophagic response that counteracts differentiation process.